PENINGKATAN KEMAMPUAN KOGNITIF PESERTA DIDIK MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH DENGAN PENDEKATAN KONTEKSTUAL - Yenny Suzana; Almira Amir (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2022)
The problem of cognitive abilities of students in class V MIN-6 East Aceh in the learning process is caused by the implementation of the learning being applied that does not show meaningfulness and students are not fully involved in solving math problems. The research objective is to improve the cognitive abilities of students through a problem-based learning model with a contextual approach to the volume of cubes and block. The implementation of this research in August 2021 to November 2021 takes place in class V MIN-6 East Aceh. This research uses Classroom Action Research (CAR) with Kurt Lewin's model. The implementation of this research was carried out in two cycles and each cycle carried out two meetings. Each meeting uses four stages, namely planning, action, observation and reflection. The data collection instrument used tests and observation sheets. The data analysis technique in this study used qualitative and quantitative descriptive analysis. The results of the study showed that there was an increase in the cognitive abilities of students with the implementation of a problem-based learning model with a contextual approach. Before the cycle, the cognitive scores of students who passed were 10 (40%) and a classical score of 65 was obtained. The increase in the cognitive value of students in the first cycle of the first meeting was obtained by 12 people with a value of 68 (48%). The results of the first cycle of the second meeting increased to 16 students with a value of 72 (64%). The results of the second cycle have reached the target of increasing to 21 students with a score of 80 (84%).Keywords: Problem-Based Learning, Contextual, Student Cognitive.